Building resilience in urban areas : exploring climate change adaptation strategies for buildings in urban areas of Tshwane, South Africa - Vermeulen, Abrie (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2024.